Usefulness of the SAF score to characterize NAFLD/NASH in non-cirrhotic HCV patients - Ahmed El Ray; Valerie Paradis; Ahmed Montasser; Maged Elghannam; Mohamed Shemis; Iris Nessim; Hoda Abu-Taleb; Tarik Asselah; Ashiq Mohamed; Nicolas Poté; Maha Akl; Patrick Marcellin (Egyptian Liver Journal, 2022)
Abstract Background The SAF score (steatosis, activity, and fibrosis) has been developed for the assessment of the histological severity of nonalcoholic fatty liver disease (NAFLD) and nonalcoholic steatohepatitis (NASH). The aim of this study was to assess the usefulness of the SAF score in a homogenous cohort of Egyptian patients with chronic HCV infection (CHC) without any alcohol consumption and without cirrhosis. We performed a prospective cross-sectional study including 70 consecutive Egyptian patients with chronic HCV infection to assess the usefulness of the SAF score to characterize NAFLD/NASH in non-cirrhotic HCV patients. The inclusion criteria included positive serum anti-HCV IgG antibody and positive HCVRNA, absence of treatment, and absence of cirrhosis (fibrosis score < F4). Patients were divided into two groups: with metabolic syndrome (MS) and without metabolic syndrome (non-MS). All patients were exposed to thorough history taking, full clinical examination, and laboratory and ultrasound assessment. Histopathologic evaluation of the liver biopsy for the assessment of steatosis, activity, grade, and fibrosis stage was assessed by 2 pathologists with experience in liver diseases. Results We found that the degree of fibrosis increases with aging. Liver biopsies from CHC patients with metabolic syndrome (MS) exhibited a significantly higher stage of fibrosis than biopsies from those without MS; however, the grade of inflammation did not differ significantly between the two groups. No significant correlation was found between the SAF score and the body mass index (BMI) or serum HCV RNA. No significant relation between SAF score, fibrosis, and MS. No significant relation was found between the MS and the level of HCV viremia. Conclusion We concluded that steatosis was associated with the fibrosis stage, independently of MS. This suggests that in this population, steatosis might be more related to HCV infection than to NAFLD and that fibrosis progression might be related, at least in part, to the steatosis process, i.e., virus-associated fatty liver disease (VAFLD).